Companionable forms: Writers, readers, sociability, and the circulation of literature in manuscript and print in the romantic period - Stone, H (2015)
Following recent critical work on writers' representations of sociability in Romantic literature, this thesis examines in detail the textual strategies (such as allusion, acts of address, and the use of 'coterie' symbols or references) which writers used to seek to establish a friendly or sympathetic relationship with a particular reader or readers, or to create and define a sense of community identity between readers. The thesis focuses on specific relationships between pairs and groups of writers (who form one another’s first readers), and examines 'sociable' genres like letters, manuscript albums, occasional poetry, and periodical essays in a diverse series of author case-studies (Anna Barbauld, Samuel Taylor Coleridge, Charles Lamb, John Keats and Leigh Hunt). Such genres, the thesis argues, show how manuscript and print culture could frequently overlap and intersect, meaning that writers confronted the demands of two co-existing audiences—one private and familiar, the other public and unknown—in the same work. Rather than arguing that writers used manuscript culture practices and produced 'coterie' works purely to avoid confronting their anxieties about publishing in the commercial sphere of print culture, the thesis suggests that in producing such 'coterie' works writers engaged with and reflected contemporary philosophical and political concerns about the relationship between the individual and wider communities. In these works, writers engaged with the legacy of eighteenth-century philosophical ideas about the role (and limitations) of the sympathetic imagination in maintaining social communities, and with interpretative theories about the best kind of reader. Furthermore, the thesis argues that reading literary texts in the specific, material context in which they are 'published' to particular readers, either in print, manuscript, or letters, is vital to understanding writer/reader relationships in the Romantic period. This approach reveals how within each publication space, individual texts could be placed (either by their writers, by editors, or by other readers) in meaningful relationships with other texts, absorbing or appropriating them into new interpretative contexts.